Effective Management of Disused Sealed Radioactive Sources in Uganda - Susan Nalumansi (International Journal of Nuclear Security, 2025)
Sealed radioactive sources are used in a wide range of applications in Uganda, such as medicine, agriculture, geology, industry, and other fields. After a given useful period, the sealed sources can no longer perform their intended purpose and are thus regarded as disused. However, depending on the activity of the source, the disused sources are highly active and can cause significant damage to human health and the environment when mismanaged. A regulatory body was established with the mandate to regulate peaceful applications of ionizing radiation in Uganda. Given the vulnerability of sealed sources at the end of their life cycle from both safety and security perspectives, this paper discusses various recommendations to provide logical and enhanced security measures to increase nuclear security of disused sealed radioactive sources for a safe environment.
Keywords: Disused Sealed Radioactive Sources; Management